Ieee Infocom 2004
DOI: 10.1109/infcom.2004.1354526
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotics of query strategies over a sensor network

Abstract: We consider the problem of a user querying for information over a sensor network, where the user does not have prior knowledge of the location of the information. We consider three information query strategies: (i) a Source-only search, where the source (user) tries to locate the destination by initiating query which propagates as a continuous time random walk (Brownian motion); (ii) a Source and Receiver Driven "Sticky" Search, where both the source and the destination send a query or an advertisement, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 19 publications
0
45
0
Order By: Relevance
“…They have shown that querying delay, transmission overheads can be reduced by spreading routing information through the network. This phenomenon has been quantitatively studied in [17].…”
Section: B Related Workmentioning
confidence: 99%
“…They have shown that querying delay, transmission overheads can be reduced by spreading routing information through the network. This phenomenon has been quantitatively studied in [17].…”
Section: B Related Workmentioning
confidence: 99%
“…In sensor networks, data caching has one more important benefit that is saving communication energy cost. Many existing research works focused on strategies of replicating frequently accessed sensed readings in some sensor nodes closer to base stations Ganesan et al (2003); Liu et al (2004); Ratnasamy et al (2002); Sadagopan et al (2003); Shakkottai (2004); Zhang et al (2007). In presence of multiple base stations, a research problem of finding sensor nodes for caching sensed readings is formulated as determining a Steiner tree in a sensor network Prabh & Abdelzaher (2005).…”
Section: In-network Data Cachingmentioning
confidence: 99%
“…Different from a pure 'pull' or pure 'push' approach (both of which involve expensive flooding operations), a double ruling scheme adopts a symmetric information discovery principle with both the source and sink actively searching for each other, as first suggested in rumor-routing [1]. The notion of trails has appeared in a number of other papers as well, including in trajectory forwarding [14], in the asymptotics of query strategies [16], and the combs and needles work [10]. A number of double ruling schemes that guarantee distance sensitivity have been devised in the literature [15].…”
Section: Double Rulingsmentioning
confidence: 99%